2023
DOI: 10.1002/aenm.202302996
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing Photocarrier Transport in Mesoporous Single‐Crystalline LaTiO2N for High‐Efficiency Photocatalytic Water Splitting

Ran Wang,
Hanna He,
Li Shi
et al.

Abstract: LaTiO2N is a promising narrow‐bandgap semiconductor photocatalyst that shows great promise for water redox reactions. However, its performance is often hindered by fast photocarrier recombination events. Herein, LaTiO2N mesoporous single crystals (MSCs) are successfully fabricated via a topotactic conversion route by using the Ruddlesden–Popper compound NaLaTiO4 as the precursor. The LaTiO2N MSCs are characterized by high crystallinity, abundant mesopores, no grain boundaries (GBs), and exposure of (010) and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…[40][41][42][43] On the other hand, in the case of the photocatalyst with few defects, the photocatalytic activity is not so much dependent on particle size, as recombination is suppressed even with large crystal sizes. 44,45 Fig. 8 Thus, photocatalytic activity is rarely determined by a single factor.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43] On the other hand, in the case of the photocatalyst with few defects, the photocatalytic activity is not so much dependent on particle size, as recombination is suppressed even with large crystal sizes. 44,45 Fig. 8 Thus, photocatalytic activity is rarely determined by a single factor.…”
Section: Resultsmentioning
confidence: 99%
“…52,74,82,96–98 For example for LaTiO 2 N Kasahara et al estimated that 12% of the generated holes went into N 2 evolution (for 440 μmol O 2 , 40 μmol N 2 ), 52 while for various morphologies with and without cocatalyst decoration achieving a broad range of O 2 evolution rates (15–736 μmol h −1 ), N 2 evolution in the order of 2–8 μmol was reported during the first hours. 68 Also Wang et al observed substantial N 2 evolution during the first two of four 5 h photocatalytic full water splitting cycles performed by LaTiO 2 N. 95 This observation is attributed to the corrosion via photo-oxidation of the material which is correlated to the loss of nitrogen from the structure, that seems to stop after one or two hours. Similar observations were reported for BaTaO 2 N. 96 During chronoamperometric PEC measurements of LaTiO 2 N containing electrodes, small quantities of N 2 evolution were detected as well.…”
Section: Methods and Standards To Investigate Stability And Degradati...mentioning
confidence: 99%
“… 94 Concerning long term stability a slight drop in hydrogen evolution rate for Pt decorated LaTiO 2 N catalysts in the course of four 25 min measurement cycles was reported 52 and no drop in oxygen and hydrogen evolution rate for RhCrO y and CoOOH decorated LaTiO 2 N in the course of four 5 h measurements. 95 Hence, one of the difficulties to assess consistently and comparably O 2 or H 2 evolution rates, and therefore indirectly stability, is that even when fixing the material composition there is still a large parameter space which needs to be controlled and reported to assure reproducibility. Some performance indicators of oxynitride photocatalysts have been summarized in Table 1 .…”
Section: Methods and Standards To Investigate Stability And Degradati...mentioning
confidence: 99%